2020
DOI: 10.3390/ijms22010201
|View full text |Cite
|
Sign up to set email alerts
|

From Obesity to Hippocampal Neurodegeneration: Pathogenesis and Non-Pharmacological Interventions

Abstract: High-caloric diet and physical inactivity predispose individuals to obesity and diabetes, which are risk factors of hippocampal neurodegeneration and cognitive deficits. Along with the adipose-hippocampus crosstalk, chronically inflamed adipose tissue secretes inflammatory cytokine could trigger neuroinflammatory responses in the hippocampus, and in turn, impairs hippocampal neuroplasticity under obese and diabetic conditions. Hence, caloric restriction and physical exercise are critical non-pharmacological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 369 publications
(272 reference statements)
1
32
0
1
Order By: Relevance
“…Hippocampal plasticity is strongly linked to the metabolic condition of adipose tissue [20,21]. Adolescence is a critical window for shaping both adipose tissue properties and hippocampal plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal plasticity is strongly linked to the metabolic condition of adipose tissue [20,21]. Adolescence is a critical window for shaping both adipose tissue properties and hippocampal plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HFD consumption leads to chronic low-grade peripheral inflammation, which has been regarded as a risk factor for cognitive decline ( Saltiel and Olefsky, 2017 ; Duan et al, 2018 ; Tan and Norhaizan, 2019 ). Emerging evidence showed that the peripheral or systemic inflammation produced from adipose tissue and gut triggers microglial activation and neuroinflammation and exacerbates cognitive deficits in obese individuals ( Chunchai et al, 2018 ; Guo et al, 2020 ; Lee and Yau, 2021 ). Reducing the imbalance of gut microbiota induced by HFD consumption alleviates hippocampal oxidative stress and microglial activation and restores cognitive function ( Chunchai et al, 2018 ).…”
Section: Microglial Function In High-fat Diet Consumption-associated Cognitive Declinementioning
confidence: 99%
“…Since hippocampus plays an important role in regulating spatial learning and memory processes, several studies have shown obesity associated altered insulin signaling leads to altered hippocampal function. Specifically, studies have shown that diabetes induces structural and synaptic deficits in hippocampus which results in learning and memory deficits (Lee and Yau, 2020). Furthermore, under physiological condition of obesity and diabetes, murine models have been demonstrated to have significantly decreased cell proliferation, neuronal differentiation and cell survival in hippocampus (Ho et al, 2013).…”
Section: Obesity Associated Cognitive Decline and Neurodegenerationmentioning
confidence: 99%
“…are highly sensitive to alterations in the biochemical, neurochemical, neuropathological, and/or cellular environment (Alexandrov et al, 2012;Lukiw, 2013a,b;Kumar and Reddy, 2020). As discussed in the previous section, growing evidences suggest that, obesity and other diet-induced metabolic dysfunctions can trigger and aggravate the development of neurodegenerative diseases (Ashrafian et al, 2013;Mazon et al, 2017;Lee and Yau, 2020). Hence, the exploration of some major miRNA, which are having possible role in obesity associated neurodegenerative disorders, may help to highlight perspectives of studying microRNA regulation in multiple brain signaling pathways.…”
Section: Obesity Associated Cognitive Decline and Neurodegenerationmentioning
confidence: 99%